Creating an immersive virtual reality application for ski jumping - Staurset, E. M. (Norwegian University of Science and Technology, Department of Computer and Information Science, 2015)
Virtual reality(VR) has been successfully applied to a broad range of training domains. VR provides an opportunity to train in a safe and controlled environment, with support for accurate performance measurement. In this report I present a prototype of a VR application for ski jumping. The goal for this project is to explore if such an application can be used to teach the basics of ski jumping, and if it can be used as a training tool for athletes. The development process is thoroughly described in the report. Through user testing and an expert evaluation it was concluded that the application has potential to be used as a tool for practicing the timing of the jump. Improvements for the prototype is proposed, which should enable the prototype to also evaluate the jumping technique.